MUTU ORGANOLEPTIK BROWNIES PANGGANG YANG TERBUAT DARI TEPUNG TERIGU, MOCAF DAN TEPUNG KELOR - Ni Luh Putu Sherly Yuniartini; Afe Dwiani (Jurnal Agrotek Ummat, 2021)
Brownies are chocolate cakes that are very popular and liked by almost everyone. The main raw material of processing brownies is flour which until now is still imported. The addition of mocaf and moringa leaf flour can to reduce flour use and increase organoleptic of brownies. The aim of this study was to find out the effect of substitution of wheat flour, mocaf and moringa leaf flour on organoleptic brownies. The method that used in this experiment is a Complete Random Design (CRD) with one factor that was substitution of flour, mocaf and moringa leaf flour whose treatment is A0 (Flour 50% : Mocaf 50%: Moringa leave flour 0%/control), A1 (Flour 47,5% : Mocaf 47,5% : Moringa leave flour 5%), A2 (Flour 45% : Mocaf 45% : Moringa leave flour 10%), A3 (Flour 42,5% : Mocaf 42,5% : Moringa leave flour 15%), A4 (Flour 40% : Mocaf 40% : Moringa leave flour 20%), dan A5 (Flour 37,5% : Mocaf 37,5% : Moringa leave flour 25%). The data of the research were analyzed using Analysis of Varience at level 5% and tested continued using Tukey’s Honestly Significant Difference Test (Tukey’s HSD) at the same level if there was a real difference. The results showed that substitution of flour, mocaf and moringa leaf flour on brownies has a real effect on organoleptics in hedonic test on color, texture and taste as well as organoleptic scoring on color, aroma, texture and taste, but has no effect on hedonic test in aroma. For the quality of organoleptic brownies it is known that the best treatment on hedonic tests of texture and taste parameters produced by treatment A1 (Flour 47,5% : Mocaf 47,5% : Moringa leave flour 5%) with likes criteria and for scoring tests are produced by the same treatment on aroma, texture and taste parameters with their respective criteria that are typical brownies, moist and sweet taste. The best treatment on color scoring tests is produced by treatment A5 (Flour 37,5% : Mocaf 37,5% : Moringa leave flour 25%) whith criteria are brown.